Pengaruh Implementasi Kebijakan Ketertiban Umum Terhadap Efektivitas Penertiban Pedagang Kaki Lima - Astri Siti Fatimah (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2019)
This research examines the influence of implementation of peace and public order policy on the effectiveness of regulating street vendors. The research methods used in this study are quantitative methods. The population in this study was the regulating coordination team of 137 people. The samples in his research were 33 people. Data collection techniques are used in three ways: observation, interviews, polls and documentation. Meanwhile, data analysis techniques using statistical analysis with the Path analysis model with the first tested validity and reliability. Based on a number of research results and hypotheses test results, it can be concluded that the implementation of public harmony and order policy has a significant influence on the effectiveness of PKL in Tasikmalaya City by 84.78% The remaining 15.22% is influenced by other variables such as the control given by the management and the supervision in the field is not optimal. The influence of policy implementation and public order towards the effectiveness of PKL in Tasikmalaya City is determined by dimentions, among others: communication, resources, disposition and bureaucratic structure. The greatest contribution is given by the dimensions of the then successive disposition followed by the dimension of resources, communication and bureaucratic structures. Thus the hypothesis that the author is tested and acceptable is the truth empirically.